ANALISIS KESESUAIAN BUKU TEKS BAHASA ARAB BERBASIS KETERBACAAN MENGGUNAKAN KETENTUAN FOG INDEX - Supriadi, Rinaldi; Fitriyani, Nur (Arabi : Journal of Arabic Studies, 2021)
This study discusses the general description of the textbook and then the description of the level of readability based on the readability formula and the reader's response. The method used is the descriptive method with a qualitative approach. The general description of the textbook based on the results of studies of the profile and anatomical structure is very good. Even though there is some lack in its anatomical structure, this is very reasonable considering the textbooks are presented as needed. The level of readability based on the Fog Index theory shows that textbooks are classified as very easy, while based on the reader's response through the Cloze Test the textbook is at the instructional level. This the researcher can judge that the book is suitable for use in learning. In practice the teacher's role is still needed in modifying the presentation of the material also requires the guidance of the teacher in the learning process.